Surgical guide to circumcision - Bolnick, David A. (Springer London, 2012)
Surgical Guide to Circumcision is a compendium of the who, what, where, why, and most importantly, the how of circumcision. Given that one third of the world's males have undergone this most ancient of surgical procedures, a contemporary resource on the subject is in order. Most circumcisions are elective with no acute medical necessity; that is, most are done for cultural reasons. Thus, in addition to being a standard surgical guide for those who perform circumcision, this book is an anthology of circumcision, from its prehistoric roots to its present day admixture of religion, culture, and medicine. Surgical Guide to Circumcision is a fully illustrated, step-by-step guide to the most common techniques of circumcision and addresses aspects such as informed consent, religious and cultural sensitivities, pre-exam, post-care, pain control, and prevention and management of potential complications. Written by experts in the field, Surgical Guide to Circumcision will appeal to family physicians, pediatricians, obstetricians, midwives, nurses, urologists, and anyone with a general interest in circumcision.